Vključevanje kulturne dediščine pri pouku tehnike in tehnologije na primeru raglje na vozičku - Fiksl, Majda (Revija za elementarno izobraževanje, 2010)
Cultural heritage included in course of design and technology sampled with a rattle on wheels. Creativity is a basic human ability, but there are some capabilities and personal characteristics needed that we all more or less have. A lot of creativity is used in manufactured products and they remind us of our cultural heritage. With this project work I wish to encourage curiosity and imagination as well as a sense of cultural heritage. Revised study plans in primary school technology classes have strengthened the work in our regular classes and elective classes. Pupils now search for the material and technologies that are typical for the environment where they are living and for the products they are creating. In this way, the accomplishments of our ancestors are transferred to younger generations through school practice. The article presents one of those possibilities. It is sincerely hoped that as many pro- ducts as possible that are connected with our past will be included in our work.